2003
DOI: 10.1118/1.1600738
|View full text |Cite
|
Sign up to set email alerts
|

A stereotactic method for the three‐dimensional registration of multi‐modality biologic images in animals: NMR, PET, histology, and autoradiography

Abstract: The objective of this work was to develop and then validate a stereotactic fiduciary marker system for tumor xenografts in rodents which could be used to co-register magnetic resonance imaging (MRI), PET, tissue histology, autoradiography, and measurements from physiologic probes. A Teflon fiduciary template has been designed which allows the precise insertion of small hollow Teflon rods (0.71 mm diameter) into a tumor. These rods can be visualized by MRI and PET as well as by histology and autoradiography on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
45
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(45 citation statements)
references
References 8 publications
0
45
0
Order By: Relevance
“…Nevertheless, intermodality image registration cannot rely on image content, as to avoid alignment of regions that have similar content but are not biologically colocalized. Landmarkbased registration remains the most objective registration method for multimodality imaging (7).…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, intermodality image registration cannot rely on image content, as to avoid alignment of regions that have similar content but are not biologically colocalized. Landmarkbased registration remains the most objective registration method for multimodality imaging (7).…”
Section: Discussionmentioning
confidence: 99%
“…In the past two decades, there have also been many studies specifically dealing with in-vivo brain MRI to post-mortem histology. The majority of these studies focused on primates (Dauguet et al, 2007;Malandain et al, 2004;Breen et al, 2005;Ceritoglu et al, 2010;Choe et al, 2011) or rodents (Jacobs et al, 1999;Humm et al, 2003;Meyer et al, 2006;Lebenberg et al, 2010;Yang et al, 2012;Liu et al, 2012). The few studies that registered human brain MRIto histology were performed on wholebrain (Schormann et al, 1995;Kim et al, 2000;Singh et al, 2008), or single hemisphere (Yelnik et al, 2007;Osechinskiy and Kruggel, 2011) post-mortem serially sectioned data (Amunts et al, 2013) created a 3D model of single subject's brain using post-mortem histological sections reconstructed at 20 m isotropic resolution and registered it to a T1 average atlas created from 24 subjects.…”
Section: Introductionmentioning
confidence: 99%
“…In an earlier study, Humm et al demonstrated an elegant registration procedure where fiducials were embedded into the tissue. Submillimeter registration accuracy was reported (2). In describing the method to transform magnetic resonance imaging (MRI) coordinates to tissue sections for histology, they showed a figure with the tissue embedded in optimal cutting tissue cryofixative.…”
Section: Introductionmentioning
confidence: 99%